A COMPARATIVE STUDY ON INTROVERT AND EXTROVERT STUDENTS PERSONALITY IN ENGLISH LISTENING SCORES - Yessi Travolta; Mulyadi .; Imranuddin . (Universitas Bengkulu, 2018)
The objectives of this research were to investigate whether there were any significant differences between introvert and extrovert students on their listening score and to find out which of the students who have better in English listening scores. This research was a descriptive comparative research. The samples of this research were 66 students consisting of 33 introvert students and 33 extrovert students at the fourth semester students of English education study program in Bengkulu University. The instruments of this research were personality questionnaire by Laney (2002) was used to determine the introvert and extrovert personality, and TOEIC Listening simulation was used to find out the students’ listening scores. The researcher used SPSS Independent Group t-test with significant level 0.05. The result of the analysis indicated that Sig. P (2-tailed) was 0.003 > 0.05. Furthermore, the computation showed that the mean score of introvert was 364.39, and the mean score of extrovert was 322.12. Therefore, the mean score of introvert group was higher than extrovert group. It could be concluded that the results of the research were: (1) There was significant difference between introvert and extrovert students on their English listening scores, (2) The introvert students have better in English listening score than the extrovert students.